ANALISIS PENGARUH SISTEM PENILAIAN KINERJA SECARA DIGITAL, PELATIHAN DIGITAL DAN EVALUASI KINERJA TERHADAP PERFORMA KARYAWAN PADA INDUSTRI MANUFAKTUR - Djunaedi Djunaedi; Fahrina Mustafa; Muhammad Kholil; Desi Kristanti; Basuki Wisnu; Arifin Arifin (POLITEKNIK LP3I JAKARTA, 2025)
In the era of increasing digitalization, the manufacturing industry faces challenges to improve employee efficiency and performance through information technology. This study aims to analyze the effect of digital performance appraisal systems, digital training, and performance evaluations on employee performance in the manufacturing industry. The research method used is quantitative, using a survey approach involving 120 respondents from various positions in manufacturing companies that have implemented digital systems in HR management. The instrument used was a questionnaire with a Likert scale, which was then analyzed using the multiple linear regression method. The results of the study indicate that the digital performance appraisal system has a significant positive effect on employee performance. Digital training also shows a positive correlation in improving employee skills and productivity. Regular performance evaluations strengthen constructive feedback and increase work motivation. The three independent variables simultaneously contribute significantly to improving employee performance. These findings support the importance of digital transformation in human resource management in the manufacturing sector. The implications of this study provide an overview that digital adaptation not only supports process efficiency but also improves employee capabilities and work results. Thus, companies must continue investing in digital systems integrated with employee performance improvement strategies.